2020
DOI: 10.1007/s11665-020-04667-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Shock Peening on the Microstructure and Properties of the Inconel 625 Surface Layer

Abstract: The aim of this work was to investigate the influence of laser shock peening on the topography, microstructure, surface roughness and the mechanical properties of the Inconel 625 nickel alloy. Examination of the topography and microstructure of the nickel alloy after laser treatment was carried out by means of scanning electron microscopy as well as atomic force microscopy. The roughness of the surface was measured by WYKO NT9300 equipment. Nanohardness test was carried out using a nanoindenter NHT 50-183 of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Shot peening increases the fatigue strength of elements made of nickel alloys working at elevated temperatures [ 20 ]. Nickel alloys are treated with laser shot peening as well [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shot peening increases the fatigue strength of elements made of nickel alloys working at elevated temperatures [ 20 ]. Nickel alloys are treated with laser shot peening as well [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laser peening is the cold forming process used to treat the surface, and compressive residual stress can be achieved by the shock wave due to the expansion of high-pressure plasma. In the laser peening process, a focused, high-energy, and short-pulsed laser beam irradiates the surface of a metal specimen, which is usually covered with a thin layer of overlay water [ 27 ], glass [ 28 ], paint [ 29 ], aluminum foil [ 30 , 31 ], or tape [ 32 , 33 ] for protection against melting [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…LSP generates microstructure modification, including grain size reduction [ 17 , 18 ], dislocation proliferation and rearrangement [ 19 , 20 , 21 ] and mechanical twin generation [ 22 ]. Górnikowska et al [ 23 ] investigated the influence of LSP on the topography, microstructure, surface roughness and the mechanical properties of the Inconel 625 nickel alloy. It was concluded that the LSP caused severe plastic deformation of the surface layer, resulting in the slip bands on the surface and cross-section of the treated material, a high density of dislocations and a higher hardness of the treated region.…”
Section: Introductionmentioning
confidence: 99%